THE IMPACT OF ENVIRONMENTAL ACCOUNTING AND INVESTMENT DECISIONS ON ENHANCING FIRM VALUE IN PHARMACEUTICAL SUBSECTOR COMPANIES - Joicenda Nahumury (Center for Indonesian Accounting Studies, 2025)
Research Objective: This study aims to obtain empirical evidence of the determinant factors of firm value of healthy entities, especially in the pharmaceutical subsector during the -19 pandemic in the period 2017-2021. Method: Multiple linear regression was used for data analysis with SPSS 25 as the testing tool Findings: The result of hypothesis testing indicates that probability, environmental accounting and investment decisions have positive effect on firm value, while capital structure has no effect on firm value Theoretical and Policy Implications: depth explanation of of Signalling Theory as the part of Agency theory(especially in explanation of three independent variables: probability, environmental accounting and investment decisions) Research Novelty: This study choses environmental accounting as independent variable that rarely imposed in previous similar studies